"It's really exciting to think where it could go": a mixed-method investigation of clinician acceptance, barriers and enablers of virtual reality technology in communication rehabilitation. Issue 15 (17th July 2022) - Vaezipour, Atiyeh; Aldridge, Danielle; Koenig, Sebastian; Theodoros, Deborah; Russell, Trevor
Abstract: Purpose: Acquired communication disorders can result in significant barriers to everyday life activities, and commonly require long-term rehabilitation. This research aimed to investigate usability, acceptance, barriers and enablers to the use of immersive virtual reality (VR) technology for communication rehabilitation from the perspective of speech-language pathologists (SLPs). Methods: Semi-structured interviews and surveys (system usability and motion sickness) were carried out with 15 SLPs following their participation in communication activities typical of daily life, experienced within an immersive VR kitchen environment. Results: The system usability scores were average. In addition, motion sickness symptoms were low after interaction with the VR system. The main findings from semi-structured interviews are discussed across five main themes: (i) attitude towards the use of VR in communication rehabilitation (ii) perceived usefulness of VR (iii) perceived ease of use of VR (iv) intention to use VR, and (v) clinical adoption barriers and enablers. Conclusions: Overall, participants were positive about VR and its potential applications to communication rehabilitation. This study provides a foundation to inform the design, development, and implementation of a VR system to be used in the rehabilitation of individuals with acquired communication disorders. IMPLICATIONS FOR REHABILITATION: Virtual Reality applications could simulate social communication situations within the clinic. VR could be used as a rehabilitation tool for communication assessment and/or outcome measure. VR requires customisation to the specific communication rehabilitation needs of the client. Participants identified barriers and enablers to adoption of VR by speech-language pathologists.